HOW THE RESEARCH SKILLS DEVELOPMENT FRAMEWORK MAY BE USEFUL FOR INDONESIAN HIGHER EDUCATION LEARNING PRACTICE - Oskar Hutagaluh; Sardjana Orba Manullang; Muliyadi Hamid; Abdul Samad Arief; Dayan Abdurrahman (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
This qualitative research aimed to review the usefulness of Research Skills Development framework (RSD) among higher education students in Indonesia. The RSD concept has contributed to research-based learning models among students in Australia, both among elementary and tertiary school students. Due to this research framework's success in Australia, we plan to review and see the usefulness of the RSD framework to university students in Indonesia. To facilitate this introduction, we have tried to review several important documents related to this RDS concept, application, evaluation together with rubric assessment. Furthermore, we reported it as a document to the introduction to the research development framework. The results of this document review will be published in one of the higher education academic journals in Indonesia. With the hope that this document will be the forerunner of introduction and development among students, especially those who are completing academic assignments involving research skills for publication purposes to assess academic communication skills. However, many things will challenge this kind of study, something new to the concept of confirmative studies in Indonesia, including several new terms in the research framework that require new understanding notations.